The mediating role of green supply chain and supply chain collaborative innovation - Sittichai Pintuma; Chanicha Moryadee; Wawmayura Chamsuk; Patchara Phochanikorn; Mohd Rizaimy Shaharudin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Manufacturers and consumers have become increasingly aware of the environmental impact of manufacturing and consumption. However, most businesses lack the commitment to adopt sustainable practices and transform themselves into a green business. This study aims to examine the factors that can influence sustainable supply chains within the plastic packaging industry of Thailand and formulate effective sustainable supply chain strategies. This research adopts a quantitative approach and examines 220 business operators in the Thai plastic packaging industry. Data are collected with a questionnaire and analysed using a structural equation model. Findings indicate that latent factors such as stakeholder-driven initiatives, green supply chain practices and supply chain collaborative innovation have a significant positive impact on sustainable supply chain management. In addition, the innovative use of renewable resources within the supply chain can facilitate the transformative shift in business operations and integration of economic and environmental activities to establish a sustainable industry network. The results can serve as valuable guidelines for entrepreneurs for facilitating product development, multichannel distribution, cost reductions, time efficiency and revenue growth. Future research should conduct cross-industry comparisons to analyse demand for and emphasis on green product manufacturing and explore variations in consumers’ attitudes towards eco-friendly products and entrepreneurs’ attitudes towards the plastic manufacturing industry.